2022
DOI: 10.1007/s10753-022-01718-w
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Role of Oxidative Stress, Cytokine Expression, and Impaired Hematological Indices in Diabetic Cardiovascular Diseases

Abstract: A simultaneous increase in the prevalence of diabetes mellitus (DM), a risk factor for cardiovascular diseases (CVDs), has contributed to the escalation of CVD related mortalities. To date, oxidative stress and inflammation are increasingly recognized as significant drivers of cardiovascular complications in patients with diabetes. Therefore, this study aims to explore the correlation between oxidative stress, inflammation, and hematological indices in diabetic patients with CVDs. Patients were allocated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…When compared to healthy individuals, MDA concentrations were significantly greater in the group of MI patients who had T2DM. Our results were consistent with research conducted by Saad et al, who noted that MDA increased in MI patients with a notable elevation in the diabetic group when compared to the non-diabetic and healthy control groups [50]. Another study by Mahreen et al [51] also found an elevated MDA levels in diabetics with MI than healthy control groups.…”
Section: Discussionsupporting
confidence: 93%
“…When compared to healthy individuals, MDA concentrations were significantly greater in the group of MI patients who had T2DM. Our results were consistent with research conducted by Saad et al, who noted that MDA increased in MI patients with a notable elevation in the diabetic group when compared to the non-diabetic and healthy control groups [50]. Another study by Mahreen et al [51] also found an elevated MDA levels in diabetics with MI than healthy control groups.…”
Section: Discussionsupporting
confidence: 93%
“…Cardiovascular disease (CVD) refers to a group of diseases with high mortality rate 32 . Abdominal aortic aneurysm (AAA) refers to pathologically dilated arterial wall of the lower abdomen of the aorta.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…Cardiovascular disease (CVD) refers to a group of diseases with high mortality rate. 32 Abdominal aortic aneurysm (AAA) refers to pathologically dilated arterial wall of the lower abdomen of the aorta. IL‐38 may protect against AAA formation by regulating the accumulation and phenotype of macrophage through IL1RL2‐p38 pathway, therefore, it is speculated that IL‐38 may be a new therapeutic modality for the treatment of AAA.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…Oxidative damage in the cardiovascular system may occur when antioxidant defense is perturbed to limit ROS production. Oxidant stress has been linked to the pathogenesis of age-associated cardiovascular complications and heart disease [13,[38][39][40]. In this context, early observational studies centered on dietary antioxidants (β-carotene, ascorbic acid, α-tocopherol) and showed an inverse relationship between intake of these antioxidants and adverse cardiovascular events [15,41].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine dysregulation is believed to play a dominant role in the remodeling of the cardiac function at older age, with evidence pointing to an inadequancy to fine-control systemic inflammation reflecting unhealthy aging [49,50]. This reshaping of cytokine expression pattern, with a progressive decline in antioxidant capacity can calibrate the functional performance of the heart [38][39][40]. Chronic low-grade systemic inflammation is a well-established hallmark of aging [49,51] and is characterized by high levels of circulating cytokines in the aged population in the absence of general pathophysiological stress [49,50].…”
Section: Discussionmentioning
confidence: 99%